2021
DOI: 10.1002/acr.24167
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Systemic Sclerosis–Mixed Connective Tissue Disease and Systemic Sclerosis Overlap Syndromes

Abstract: Objective To describe the clinical characteristics and outcomes of systemic sclerosis–mixed connective tissue disease (SSc–MCTD) and SSc overlap syndrome. Methods We included patients from the Australian Scleroderma Cohort Study who met American College of Rheumatology/European Alliance of Associations for Rheumatology criteria for SSc. Three mutually exclusive groups were created: SSc–MCTD, SSc overlap, and SSc only. Univariate comparison of clinical features was performed by analysis of variance or chi‐squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 11 publications
1
13
0
3
Order By: Relevance
“…Interestingly, our data do suggest that patients with cSLE with anti-RNP seem to be a more severe subgroup with more SLE-related disease damage, which was also stated by Dayal and Isenberg 28. On the other hand, a recent study in SSc showed that the presence of anti-RNP antibodies fits with a subgroup of SSc with a better prognostic outcome in terms of survival 29. Thus, the detection of anti-RNP antibodies might have a different prognostic meaning in these different systemic autoimmune diseases or scleroderma spectrum disorders.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, our data do suggest that patients with cSLE with anti-RNP seem to be a more severe subgroup with more SLE-related disease damage, which was also stated by Dayal and Isenberg 28. On the other hand, a recent study in SSc showed that the presence of anti-RNP antibodies fits with a subgroup of SSc with a better prognostic outcome in terms of survival 29. Thus, the detection of anti-RNP antibodies might have a different prognostic meaning in these different systemic autoimmune diseases or scleroderma spectrum disorders.…”
Section: Discussionsupporting
confidence: 85%
“… 28 On the other hand, a recent study in SSc showed that the presence of anti-RNP antibodies fits with a subgroup of SSc with a better prognostic outcome in terms of survival. 29 Thus, the detection of anti-RNP antibodies might have a different prognostic meaning in these different systemic autoimmune diseases or scleroderma spectrum disorders. Most patients with anti-RNP antibodies in the scleroderma pattern group also had multiple, more SLE-specific, auto-antibodies detected, besides other clinical SLICC criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The ASIG registry has contributed to the field of PAH screening 123,124 , GI involvement 125 , overlap syndrome 126 , quality of life 127 , and activity impairment 128 . Furthermore, in the immunological characterization of patients, especially patients with anti-Ku, anti-RNA pol III, and anti-PM75-100 86,[129][130] , also the relation with occupational silica exposure 131 .…”
Section: Australia 2007mentioning
confidence: 99%
“…Acerca dele, a literatura sugere que os pacientes têm curso de doença e envolvimento de órgãos diferentes daqueles que atendem puramente aos critérios não superpostos. Em vista disso, esses pacientes, com SP ES-LES devem ser considerados como um subgrupo distinto [7][8][9] . A denominação SP é utilizada para aqueles que manifestam características de múltiplas DDTC mas que não apresentam o anticorpo anti--RNP em altos títulos.…”
unclassified
“…A denominação SP é utilizada para aqueles que manifestam características de múltiplas DDTC mas que não apresentam o anticorpo anti--RNP em altos títulos. Se o paciente apresentar fenômeno de Raynaud ou puffy hands, associada às manifestações clínicas de pelo menos duas das DDTC, LES e ES ou dermatomiosite, e anti-RNP em altos títulos, a entidade passa a se chamar doença mista do tecido conjuntivo 8 .…”
unclassified